2021
DOI: 10.1037/cdp0000455
|View full text |Cite
|
Sign up to set email alerts
|

A validation of the Perceived Negative Context of Reception Scale with recently-arrived Venezuelan immigrants in Colombia and the United States.

Abstract: Objectives: Millions of Venezuelans have left their country in search of safety and stability in the United States (U.S.) and Colombia, two countries where recent increases in anti-immigrant rhetoric and sentiment have occurred. The Perceived Negative Context of Reception Scale captures the degree to which immigrants report feeling that people from their country are unwanted/marginalized within their new receiving context. In the present study, we examine the psychometric properties of the Perceived Negative C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 40 publications
1
23
0
Order By: Relevance
“…Negative context of reception was measured via the six-item Negative Context of Reception Scale (Salas-Wright, Oh, et al, 2021; S. J. Schwartz et al, 2014) to assess how unwelcome participants felt in the mainland U.S. context.…”
Section: Methodsmentioning
confidence: 99%
“…Negative context of reception was measured via the six-item Negative Context of Reception Scale (Salas-Wright, Oh, et al, 2021; S. J. Schwartz et al, 2014) to assess how unwelcome participants felt in the mainland U.S. context.…”
Section: Methodsmentioning
confidence: 99%
“…An unwelcoming environment, or negative context of reception , refers to feeling shut out or excluded from opportunities in the society in which one lives, as well as a perception that one’s society does not welcome people from one’s ethnic/racial group (Portes & Rumbaut, 2014). Because it represents exclusion, negative context of reception is associated with depressive symptoms, anxiety, and lowered well-being among a variety of immigrant populations (Forster et al, 2021; Salas-Wright et al, 2021; Schwartz et al, 2014, 2018). The primary difference between negative context of reception and discrimination is that discrimination involves specific incidents that communicate exclusion, whereas negative context of reception refers to a feeling of being excluded from the dominant local or national ingroup—even if no specific incidents occur (Portes & Rumbaut, 2014).…”
Section: Cultural Stressorsmentioning
confidence: 99%
“…Previous studies have suggested that Hispanic college students reported psychosocial maladaptation such as depressive symptoms (Salas‐Wright et al, 2021) and physically aggressive behavior (Forster et al, 2015) when they had cultural‐related stressful experiences, such as cultural incongruity between their heritage and destination cultural streams (Lee et al, 2021) and a negative perceived context of reception (Schwartz, Unger, et al, 2014). For example, Hispanic students frequently face pressure to adopt aspects of American culture to create a better fit with their academic institutions (Cano et al, 2014).…”
Section: Introductionmentioning
confidence: 99%